2016
DOI: 10.1021/acs.nanolett.6b03329
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticle Assisted mRNA Delivery for Potent Cancer Immunotherapy

Abstract: The induction of a strong cytotoxic T cell response is an important prerequisite for successful immunotherapy against many viral diseases and tumors. Nucleotide vaccines, including mRNA vaccines with their intracellular antigen synthesis, have been shown to be potent activators of a cytotoxic immune response. The intracellular delivery of mRNA vaccines to the cytosol of antigen presenting immune cells is still not sufficiently well understood. Here, we report on the development of a lipid nanoparticle formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
486
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(523 citation statements)
references
References 53 publications
(98 reference statements)
7
486
0
3
Order By: Relevance
“…In the same study, coadministration of mRNA encoding granulocyte–macrophage colony-stimulating factor (GM-CSF) improved OVA-specific cytolytic responses. Another report showed that subcutaneous delivery of LNP-formulated mRNA encoding two melanoma-associated antigens delayed tumour growth in mice, and co-delivery of lipopolysaccharide (LPS) in LNPs increased both CTL and antitumour activity 153 . In general, mRNA cancer vaccines have proved immunogenic in humans, but further refinement of vaccination methods, as informed by basic immunological research, will likely be necessary to achieve greater clinical benefits.…”
Section: Mrna Cancer Vaccinesmentioning
confidence: 99%
“…In the same study, coadministration of mRNA encoding granulocyte–macrophage colony-stimulating factor (GM-CSF) improved OVA-specific cytolytic responses. Another report showed that subcutaneous delivery of LNP-formulated mRNA encoding two melanoma-associated antigens delayed tumour growth in mice, and co-delivery of lipopolysaccharide (LPS) in LNPs increased both CTL and antitumour activity 153 . In general, mRNA cancer vaccines have proved immunogenic in humans, but further refinement of vaccination methods, as informed by basic immunological research, will likely be necessary to achieve greater clinical benefits.…”
Section: Mrna Cancer Vaccinesmentioning
confidence: 99%
“…This idea has increased the efficacy of candidate immunotherapies involving whole tumor cell lysates through improved targeting to DCs [65,67]. Biomaterials have also been used to increase the efficacy of checkpoint blockade therapies by better selective targeting to specific cell types, decreasing systemic side effects [68,69]. Only now are some of these ideas filtering into clinical trials [70], highlighting the need to use more rigorous preclinical models in testing biomaterials and to push toward clinical studies.…”
Section: Biomaterials Improve Targeting Selectivity and Potency Of mentioning
confidence: 99%
“…10 Similarly, lipid nanoparticles assembled with specified compositions were recently shown to protect RNA sequences from extracellular ribonuclease degradation and promote their efficient uptake by professional antigen-presenting cells to express tailor-designed antigenic peptides in vivo. 11 Using RNA sequences that encode viral or mutant neo-antigens, these nanoparticle constructs induce strong antitumor effector and memory T-cell responses through potent IFNα activation (Figure 1a). 12 Remarkably, early clinical data from the first three melanoma patients treated with these lipid nanoparticle–RNA constructs showed strong IFNα and antigen-specific antitumor responses, 12 thus offering significant hope that such a system can be readily translated to the clinic.…”
Section: Nanomedicines As Delivery Platforms For Immunomodulating Agentsmentioning
confidence: 99%